The role of fibrinogen and fibrinogen concentrate in cardiac surgery: an international consensus statement from the Haemostasis and Transfusion Scientific Subcommittee of the European Association of Cardiothoracic Anaesthesiology. (17th September 2019) - Erdoes, G.; Koster, A.; Meesters, M. I.; Ortmann, E.; Bolliger, D.; Baryshnikova, E.; Ahmed, A.; Lance, M. D.; Ravn, H. B.; Ranucci, M.; von Heymann, C.; Agarwal, S.
Summary: To date, data regarding the efficacy and safety of administering fibrinogen concentrate in cardiac surgery are limited. Studies are limited by their low sample size and large heterogeneity with regard to the patient population, by the timing of fibrinogen concentrate administration, and by the definition of transfusion trigger and target levels. Assessment of fibrinogen activity using viscoelastic point‐of‐care testing shortly before or after weaning from cardiopulmonary bypass in patients and procedures with a high risk of bleeding appears to be a rational strategy. In contrast, the use of Clauss fibrinogen test for determination of plasma fibrinogen level can no longer be recommended without restrictions due to its long turnaround time, high inter‐assay variability and interference with high heparin levels and fibrin degradation products. Administration of fibrinogen concentrate for maintaining physiological fibrinogen activity in the case of microvascular post‐cardiopulmonary bypass bleeding appears to be indicated. The available evidence does not suggest aiming for supranormal levels, however. Use of cryoprecipitate as an alternative to fibrinogen concentrate might be considered to increase plasma fibrinogen levels. Although conclusive evidence is lacking, fibrinogen concentrate does not seem to increase adverse outcomes (i.e., thromboembolic events). Large prospective multi‐centre studies are needed to better define the optimal perioperative monitoring tool, transfusion trigger and target levels for fibrinogen replacement in cardiac surgery. Abstract : 현재까지, 심장수술에서 섬유소원(fibrinogen) 농축액 투여 의 효능 및 안전성과 관련된 자료는 한정적이다. 관련 연구들은 환자 모집단의 작은 표본 크기와 높은 이질성(heterogeneity), 섬유소원 농축액 투여 시기, 투여 기준(transfusion trigger) 및 목표 농도(target level)의 다양성으로 인해 제한을 받고 있 다. 출혈의 고위험 환자나 수술의 경우, 현장 진단용 점탄성 검 사(viscoelastic point‐of‐care testing)를 사용하여 심폐우 회술 이탈(weaning) 직전 또는 직후에 환자의 섬유소원 활성 도를 평가하는 것이 합리적인 전략이 될 수 있다. 이와 대조적 으로 Clauss 방법을 이용한 혈장 섬유소원 농도 측정은 긴 검사 소요시간, 높은 분석 간 변동성과 고농도의 heparin 및 섬유소원분해산물로 인한 간섭에 의하여 제한된 조건이 아닌이상 권장되지 않는다. 심폐우회술 후 미세출혈의 경우, 섬유 소원의 생리활성을 유지하기 위한 섬유소원 농축액 투여의 적 응증이 될 수 있다. 그러나 현재의 연구 결과들을 토대로 보았을 때, 비정상적으로 높은(supranormal) 농도를 목표로 투여하 는 것은 권장되지 않는다. 혈장 섬유소원 농도를 높이기 위해 섬유소원 농축액의 대체제로 동결침전제제(cryoprecipitate) 를 사용하는 것을 고려할 수 있다. 아직 확증되지는 않았으나, 섬유소원 농축액이 합병증(혈전색전증)을 증가시키지 않는 것 으로 보인다. 심장수술에서의 섬유소원 보충에 최적화된 수술 중 모니터링 도구, 투여 기준, 목표 농도를 더 잘 규정하기 위 한 대규모 전향적 다기관 연구가 필요하다.